GENETIC IDENTIFICATION OF SEA HOLLY (Acanthus ilicifolius) THROUGH DNA BARCODING FROM COASTAL CILACAP, CENTRAL JAVA, INDONESIA - Taufan Harisam; Florencius Eko Dwi Haryono; Bintang Marhaeni; Amron Amron; Norman Arie Prayogo; Purnama Sukardi (BIOTROPIA, 2020)
Sea holly (Acanthus ilicifolius) is an important true mangrove species commonly growing in wetlands at river mouths and coastal areas. Very limited information is available on the molecular taxonomy of sea holly growing along the coasts of Cilacap, Central Java, Indonesia. The present study aimed to identify sea holly in coastal Cilacap and to produce a reference library on the molecular characteristics of the species. The recently recorded species were utilized for the barcoding investigation. Genetic identification was evaluated using the rbcL and matK genes. Young leaf samples of A. ilicifolius were collected for DNA extraction, isolation, and amplification using rbcL and matK primers. The length of the rbcL gene was 608 bp and the matK gene was 970 bp. The evolutionary history was constructed using the Neighbor-Joining method. The barcode sequences of rbcL and matK were analyzed using BLAST and MULTALIN. The sequences were also submitted to NCBI. Genus Acanthus (Acanthaceae) and other genera were clustered in the same clade with high bootstrap values. The results indicated that the rbcL and matK loci cannot be used for species differentiation within Acanthus; however, these genes can be used to distinguish the genus level within Acanthaceae.